GRK2 Suppresses Hepatocellular Carcinoma Metastasis and Invasion Through Down-Regulation of Prostaglandin E Receptor 2 - Li, Nan (Onco Targets Ther, 2020)
BACKGROUND: Hepatocellular carcinoma (HCC) is an aggressive form of human liver cancer and the fifth most common malignancy worldwide. Novel effective treatment strategies for HCC are urgently in clinical because of its poor response to conventional therapies. G protein-coupled receptor kinases (GRKs), including GRK2 and GRK3, are known that involves in various essential cellular processes and regulates numerous signaling pathways. However, the role of GRK2/3 in invasion and metastasis of HCC still remains unclear. MATERIALS AND METHODS: Immunohistochemistry, Western blot, laser confocal microscopy and qRT-PCR were used to detect the expression of GRK2/3 and EP2 in liver tissues of HCC patients and DEN-induced HCC mice. Wound healing and transwell assay were applied to measure the migration and invasion of HCC cells after transfected with GRK2 siRNA. The downstream pathway of Akt and ERK was verified by Western blot. RESULTS: The expression of GRK2 was significantly decreased, while GRK3 was not significantly changed in HCC tissues compared with noncancerous tissues of HCC patients. Moreover, GRK2 expression was reduced during liver tumorigenesis in diethylnitrosamine-induced liver tumor model. In addition, our in vitro study showed that GRK2 expression was gradually decreased with increasing HCC cell line metastatic potential, and GRK2 knockdown significantly promoted the migration and invasion of HCC cells. Furthermore, low GRK2 expression was associated with increased expression of EP2 receptor translocation to HCC cell membrane, and the activation of Akt pathway. CONCLUSION: These data suggest that GRK2 inhibits HCC metastasis and invasion may be through regulating EP2 receptor translocation, and this effect appears to be mediated by Akt pathway.